Filtering Sinyal Menggunakan Bandpass Filter - Agus Muliadi; Khairul Muttaqin (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
Multilevel Marketing (MLM) business visualizes a business network into a hierarchical tree consisting of relationships between nodes. In its application, a branch is generated from each node which when visualized becomes a tree with a height that continues to increase and will consume space which will have an impact in terms of less than optimal data access. In order for the tree structure to be formed from relationships between nodes with hierarchically ordered data, and to streamline time in the search and data access process, an MLM business process information system was built by applying the Binary Tree algorithm. The concept in the Binary tree itself is a hierarchical organization of several nodes, where each node has no more than 2. Nodes that are under a node are called children of the node. A node above a node is called the parent of that node. A binary search tree is a search in a binary tree by tracing nodes that are placed in the left branch if the information content sent is smaller than the information at the root, or tracing the right branch if the information content is stated to be greater than the root. The goal is to implement sorted data into the information system in accordance with the hierarchy of the MLM system and in this way data retrieval can be done quickly and easily.